Jaminan Terhadap Penyandang Disabilitas dalam Memperoleh Pekerjaan - Aurelia Marthen, Gianny; Herning Sitabuana, Tundjung (LPPM Universitas Ekasakti Padang, 2024)
Every Indonesian citizen has the right to work and live a life worthy of humanity. This includes persons with disabilities. However, in reality, there are still many people with disabilities who experience difficulties and even discrimination in obtaining employment. This research aims to determine guarantees for persons with disabilities in obtaining employment. The research method used is the descriptive normative legal research method. The data type used is secondary data sourced from primary legal materials, secondary legal materials, and tertiary legal materials. The secondary data is collected through a literature study. The data is analyzed using qualitative analysis techniques. The results of this research show that the Law on Persons with Disabilities is sufficient to regulate guarantees for persons with disabilities in obtaining employment, and various government regulations have even been issued which also regulate guarantees for persons with disabilities in obtaining employment as implementing regulations.